Perceived parental acceptance and rejection and its relationship to Alexithymia disorder among adolescents with the Autism Spectrum at integrated schools in Jeddah - Qalyoubi, Khalid Mohammad (Journal of Educational and Psychological Sciences, 2021)
The study aims to reveal the relationship of parental acceptance/ rejection by the (father- mother) as perceived by the children and the disorder of Alexithymia among a sample of adolescents with an Autism spectrum, with some demographic variables (gender- economic and social level- the work of the mother). Depending on the descriptive analytical approach The sample of the study consisted of (40) male and female adolescents with Autism Spectrum Disorder. Their ages ranged between (15: less than 19 years). A measure of parental acceptance and rejection (the mother-father version) was applied to them (was translated into Arabic by Mamdouha Salama, 2011), Toranto Scale of Alexithymia (translated into Arabic by Aladdin Kafafi- Fouad Al-Dawash 2011), and The Economic and Social Level List prepared (Razan Kurdi, 2012), was applied on the sample of study. The results indicated that a statistically significant correlation between parental acceptance- rejections by the (father-mother), as perceived by the children and between their alexithymia. The results also indicated there are differences between parents in the awareness of children of the acceptance and parental refusal in the direction of the mothers. The results also indicated Parental acceptance and rejection (the image of the mother) differed according to some demographic variables (gender in the direction of males- economic and social level in the direction of the high level- mother’s work in the direction of non-working mothers). The results also indicated that Parental acceptance and rejection (the image of the father) differed according to some demographic variables (gender in the direction of female- economic and social level in the direction of the high level). Alexithymia also differed according to some demographic variables (gender in the direction of males- economic and social level in the direction of high level- mother’s work in the direction of non-working mothers).